Study on stability, fuel properties, engine combustion, performance and emission characteristics of biofuel emulsion. (December 2015) - Reham, S.S.; Masjuki, H.H.; Kalam, M.A.; Shancita, I.; Rizwanul Fattah, I.M.; Ruhul, A.M.
Abstract: This study reviewed papers related to biofuel emulsion, principally assessing the use of biofuel emulsion. The discussion is focused mainly on three active areas of emulsified biofuel, namely, exploration of various factors affecting the preparation of stable emulsion and its fuel properties, investigation of the effect of water concentration on physicochemical properties of fuel, and observation of the improvement and degradation of combustion, performance, and emission characteristics and the possible methods to enhance these characteristics.